A 32 kDa surface antigen of Theileria parva: Characterization and immunization studies - Skilton, Robert A.; Musoke, A.J.; Wells, C.W.; Yagi, Y.; Nene, Vishvanath M.; Spooner, P.R.; Gachanja, J.; Osaso, J.; Bishop, Richard P.; Morzaria, S.P. (Cambridge University Press, 2000)
Previous studies using monoclonal antibody (mAb) 4C9 specific for a 32 kDa antigen (p32) of Theileria parva demonstrated expression of the antigen on the surface of the sporozoite, making it a potential antigen for sporozoite neutralization. A full-length cDNA encoding the major merozoite/piroplasm surface antigen (mMPSA) of T. parva was cloned and expressed in bacteria. The expressed product reacted strongly with mAb 4C9, demonstrating identity between the p32 and mMPSA of T. parva. Using immunoblot analysis and immunoelectron microscopy with mAb 4C9 it was shown that the mMPSA is a major antigen of the merozoite and piroplasm at the cell surface, while lower levels of antigen are expressed in the sporozoite and schizont stages. Upregulation of the mMPSA occurs at merogony and can be induced by culturing schizont-infected lymphocytes at 42°C. Recombinant mMPSA of T. parva induced high titres of specific antibodies in cattle but failed to confer protection against a T. parva sporozoite stabilate challenge. The pre-challenge sera also failed to neutralize infectivity of sporozoites in an in vitro assay. Possible reasons for the lack of parasite neutralization in vivo and in vitro are discussed.